2008
DOI: 10.1177/1934578x0800301206
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemopreventive Potential of Humulones and Isohumulones (Hops α- and Iso-α-acids): Induction of NAD(P)H:Quinone Reductase as a Novel Mechanism

Abstract: Phytochemical analysis and chemopreventive testing of a special “α-/β-acid free” hops extract led to the identification of isohumulones (hops iso-α-acids) as potent inducers of NAD(P)H:quinone reductase (QR) activity. CD values (concentrations required to double the specific activity of QR in Hepa1c1c7 cell culture) were in the range of 1.3 to 10.2 μg/mL, with CD value of trans-isohumulone < cis-isoadhumulone < cis-isocohumulone < cis-isohumulone (+ trans-isoadhumulone). Humulones (hops α-acids) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…To a lesser degree, an extrahepatic production of ROS/RNS by HEX was observed in CPTC, BMSC and ELC (Figure 1B, 2A and 2B). In contrast to these results in primary canine cells, others reported that other hop components worked as antioxidants in vivo and in vitro [32][33][34][35].…”
Section: Oxidative Stress Measurementcontrasting
confidence: 59%
See 2 more Smart Citations
“…To a lesser degree, an extrahepatic production of ROS/RNS by HEX was observed in CPTC, BMSC and ELC (Figure 1B, 2A and 2B). In contrast to these results in primary canine cells, others reported that other hop components worked as antioxidants in vivo and in vitro [32][33][34][35].…”
Section: Oxidative Stress Measurementcontrasting
confidence: 59%
“…Isohumulones had antioxidant activity in Dahl salt-sensitive (DS) rats fed a commercial diet containing 8% NaCl and 0.3% isohumulone and in murine RAW 264.7 cells (IC 50 value of 5.9 -18.4 µg/mL) [32,33]. TRA and xanthohumol moderately attenuated the production of peroxyl, singlet oxygen and hydroxyl radicals, and peroxy nitrite/ferric ion derived from a cell-free assay, respectively [34].…”
Section: Oxidative Stress Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…28 They can inhibit LPS-induced iNOS activity in RAW 264.7 macrophages at 6-18 lg/ml and induce NAD(P)H:quinone reductase activity at 1-10 lg/ml in murine hepatoma cells with cytotoxicity seen at an LD 50 > 20 lg/ml. 29 Green tea derived from Camelis sinensis consists of 30% polyphenols termed catechins. 30 The major catechins are (À) epigallocatechin-3-gallate (EPI), (À) epicathin-3-gallate, (À) epigallocatechin, and (À) epicatechin.…”
Section: Introductionmentioning
confidence: 99%
“…During brewing, the relatively insoluble α-acids are transformed into their corresponding mixture of beer-soluble diastereomeric pairs of iso-α-acids (cis-and trans-isomers), thus resulting in six iso-α-acids originating from the three main α-acids (Figure 1). Next to their application in beers, an increase in global research interest in the health-beneficial aspects of hop-derived bitter acids has been observed 1,2 as evidenced by the increasing number of reports on various promising bioactivities with IC 50 values in the lower micromolar range (anti-inflammatory 3,4 and antiangiogenic properties, 5,6 improving lipid profiles, 7,8 and counteracting diabetes type 2). 9 In comparison to the growing knowledge on their healthbeneficial effects, little is known about the absorption, distribution, metabolism, and excretion (ADME) of these compounds.…”
Section: ■ Introductionmentioning
confidence: 99%